2023
DOI: 10.3390/microplastics2010009
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Assay to Quantify Effects of Micro- and Nano-Plastics on Human Gene Transcription

Abstract: In today’s age, plastic waste is a major problem for our environment. The decomposition of plastic waste causes widespread contamination in all types of ecosystems worldwide. Micro-plastics in the lower micrometer size range and especially nano-plastics can become internalized by cells and thus become a threat to human health. To investigate the effects of internalized micro- and nano-plastics on human gene transcription, we used an in vitro assay to quantify CREB (cAMP response element binding protein) mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…HEK293 cells were plated at a density of 3 × 10 4 per well in a 24-well plate with PMMA nanobeads (4.5 × 10 9 beads/mL). After 72 h, cells were transfected with either one of the following plasmids: CMV-MGFP as the positive control, CRE-MGFP as the inducible gene and TATA-MGFP linked to a non-inducible region as the negative control [16]. All three plasmids are part of a Cignal Reporter Assay Kit (Qiagen, Venlo, The Netherlands) and based on the stimulation of a CREB-mediated protein kinase A (PKA) signaling pathway.…”
Section: Transfection Of Hek293 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…HEK293 cells were plated at a density of 3 × 10 4 per well in a 24-well plate with PMMA nanobeads (4.5 × 10 9 beads/mL). After 72 h, cells were transfected with either one of the following plasmids: CMV-MGFP as the positive control, CRE-MGFP as the inducible gene and TATA-MGFP linked to a non-inducible region as the negative control [16]. All three plasmids are part of a Cignal Reporter Assay Kit (Qiagen, Venlo, The Netherlands) and based on the stimulation of a CREB-mediated protein kinase A (PKA) signaling pathway.…”
Section: Transfection Of Hek293 Cellsmentioning
confidence: 99%
“…The plasmids used for transfection were derived from a reporter assay kit used for the quantitative assessment of signal transduction pathways. Previously, it has been shown that the addition of PMMA nanobeads will result in abolished in vitro gene expression [16]. Transfection using the same plasmids enables assessment of whether CREB-mediated signaling is altered in HEK293 cells due to the presence of PMMA as well.…”
Section: Transfection Of Hek 293 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to information submitted by the industry to the US Food and Drug Administration (FDA) under the Voluntary Cosmetic Registration Program (VCRP), PMMA is widely used in bath soaps, make-up, hair dyes, and personal cleaning/care products. It has been used in a wide range of cosmetic products (Becker et al 2011 ; Pellegrino et al 2023 ). Recently, PMMA microplastics have been detected in the human liver (Horvatits et al 2022 ), cardiac tissue (Yang et al 2023 ), and blood (Leslie et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research has revealed the presence of MPs in human blood [13] and baby placenta [14], emphasizing the urgency to investigate their potential impacts on sensitive human organs, including the brain and heart [15,16]. Furthermore, studies have examined their influence on neurological behavior [17], the immune system [18,19] and disruption in gene transcription [20]. These findings, while significant, only scratch the surface, and a deeper exploration of this subject reveals the remarkable ability of MPs to adsorb various pollutants, acting as carriers into the human body and other living organisms [21,22].…”
Section: Introductionmentioning
confidence: 99%